Deriving Simulation Models from Business Process Models - Rittgen, Peter (INFOCOMP Journal of Computer Science, 2005)
Simulation of a business process is often used to visualize its behaviour, to identify problems and to improve its performance. It requires the design of a simulation model, a detailed model of the processes, the resources and the variables to be monitored. Here we investigate how the development of such a model can be facilitated by using a language-action model of the business process as a basis.